(untitled) (Studia austriaca, 2025)
Marlene Streeruwitz’s award-winning novel Nachwelt (1999, Posterity) is a highly avant-garde experiment in metafiction. Described on its cover as both a «novel» and a «travelogue», the text intertwines autobiographical elements with biographical elements from the life of the sculptor Anna Mahler, daughter of Gustav Mahler and Alma Mahler-Werfel. Drawing on Judith Butler’s redefinition of ‘affirmation’, this article examines how Streeruwitz develops a narrative technique in Nachwelt that both critiques conventional biographical narratives and creates an alternative form of life writing, grounded in an ‘affirmative’ textual strategy.